Efficacy of Chinese herbal medicine on nasal itching in children with allergic rhinitis: a systematic review and meta-analysis - Chen, Yuhang; Wang, Jie; Wu, Liqun; Zhang, Ye; Chen, Hong; Zhang, Ziwei (Frontiers in Pharmacology, 2023)
Background: Allergic rhinitis is prevalent among children and can cause nasal itching, fatigue, and even hinder growth and development. The main discomfort symptom of allergic rhinitis is nasal itching. Chinese herbal medicine is effective in treating allergic rhinitis. Therefore, we evaluate the clinical efficacy of Chinese herbal medicine in treating nasal itching caused by allergic rhinitis in children. Methods: Nine databases were searched from inception to March 2023 to identify eligible randomized controlled trials. The effectiveness of Chinese herbal medicines for nasal itching was mainly evaluated. The Risk of Bias tool 2.0 assessed the risk of bias. Statistical analysis using RevMan 5.3 and Stata/SE 12. The quality of evidence was evaluated by GRADEpro 3.6. Results: The review incorporated 23 studies. The meta-analysis indicated that herbal medicine was more effective than a placebo in reducing nasal itching (MD = -0.59, 95%CI: -0.94–-0.24) and increasing interleukin 10 level (SMD = 1.47, 95% CI: 0.90–2.05). Compared to Western medicine, the combining herbs and Western medicine showed better efficacy in relieving nasal itching, inhibiting immunoglobulin E, interleukin 4 and 33, enhancing interleukin 10, improving therapeutic efficiency, and reducing recurrent. Oral herbal medicine was more effective in treating nasal itching (MD = -0.45, 95% CI: -0.62–-0.29). Combining oral and external herbal medicines was more efficient in treating nasal itching (MD = -0.44, 95% CI: -0.54–-0.33), inhibiting immunoglobulin E, interleukin 4 (SMD = -0.87, 95% CI: -1.24–-0.50) and 33 (SMD = -1.16, 95% CI: -1.54–-0.77), and improving therapeutic efficiency. External herbal medicine did not show differences compared to Western medicines. Regarding safety, herbal medicine alone exhibited fewer adverse events than Western medicine; combining herbal and Western medicine showed no significant variation in adverse event incidence. Conclusions: Chinese herbal medicines can reduce nasal itching in children with allergic rhinitis, and regulate immunoglobulin E and inflammatory factors. Further, more rigorous studies are needed to validate these findings.